Memory B Cell Responses at 16 Weeks Following a Single Dose of AZD1222/Covishield in Sri Lankan Individuals. (March 2022) - Ramu, S.T.; Jeewandara, C.; Kuruppu, H.; Pushpakumara, P.; Harvie, M.; Dayarathna, S.; Jayadas, T.; Ranasinghe, T.; Aberathna, I.S.; Danasekara, S.; Dissanayake, O.; Gamalath, N.; et al.
Abstract : Purpose: The dosing interval for AZD1222/Covishield vaccine was prolonged for ≥16 weeks, due to short supply in Sri Lanka. As robust secondary immune response depends on the presence of memory B cell (Bmem), we investigated their frequency following a single dose of the AZD1222. Methods & Materials: Bmem responses were assessed to S1, S2 and N protein of the SARS-CoV-2 by B cell ELISpot assays in 45 individuals after ≥16 weeks of receiving a single dose of the vaccine. The mean±2 SD of the background responses was defined as the threshold for positive response of antibody secreting cells (ASCs)/1 million cells. Results: In this cohort, 40/45 (88.9%) individuals responded to S1, 39/45 (86.7%) to S2 and 36/45 (80%) to N. Responses to S1 (p<0.0001, median 90, IQR 50 to 137.5 ASCs/1 million cells) and S2 (p=0.0067, median 70, IQR 47.5 to 97.5 ASCs/1 million cells) were significantly higher than N (median 50, IQR 22.5 to 80 ASCs/1 million cells). A significant difference in the frequency of responses to S1 (p=0.0017) and S2 (p=0.046), were seen in different age groups, with a higher frequency of ASCs to S1 and S2 proteins in individuals age between 40-60 and >60 years of age, compared to younger individuals. There was a significant, positive correlation for the frequency of ASCs to S1 (Spearman's r=0.49, p=0.0007), S2 (Spearman's r=0.32, p=0.0308) and N (Spearman's r=0.33, p=0.0274) with age. Conclusion: 86.7% to 88.9% of individuals had Bmem to the spike protein of the virus, suggesting that a single dose of the vaccine, induced potent Bmem responses. Although 80% of individuals had a low frequency of responses to the N protein, which was not present in the vaccine, this could be due to the presence of cross reactive Bmem responses to N protein of previous beta-coronavirus infections, in older individuals.